Shame in early modern thought: from sin to sociability. Issue 3 (3rd April 2019) - Dawson, Hannah
ABSTRACT: This article challenges the historiographical narrative that modernity saw a transition from shame to guilt. I argue not only that these two concepts overlapped, but that, if anything, a shift occurred in the opposite direction: from guilt to shame. I identify two concepts of shame: guilt-shame, focused on sinfulness and caused by mere introspection, and reputation-shame, focused on social norms and caused by the (albeit imagined) gaze of others. Looking primarily at English texts, straying often into the European republic of letters, I argue that in the seventeenth century, as Biblicist fervour gave way to natural religion and a naturalistic turn in moral philosophy, and as burgeoning public spheres needed governing, reputation-shame experienced a new lease of life. This argument, in turn, questions the characterisation of the modern self as private, insulated and autonomous, gesturing instead at open, social minds that were nonetheless deeply, passionately, interiorised. In picking apart these interwoven strands in the history of the concept of shame, I hope to make the methodological point that one cannot be essentialist about concepts. There is no concept of shame that can be analysed abstracted from time and space, only particular uses of the concept in particular utterances.